Peran Tenaga Kerja dalam Pertumbuhan Ekonomi Ditinjau dari Perspektif Ekonomi Syariah - Siti Nurjanah, Sandra; Siti Nurjanah, Wulan; Azmi Muhamad Tauhid, Nurul; Laziva, Nazril; Mega Benazira, Aisyah; Dzikrayah, Fithri (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2025)
Labor plays a crucial role as one of the factors of production that influences a country's national income. Through its contributions, labor has created economic surplus, which supports the creation of cooperation within society for the provision of goods and services. This study aims to describe the role of labor in economic growth from both conventional and Islamic economic perspectives, compare the quality of labor in Indonesia with that of developed countries, and analyze the relationship between the labor market and aggregate supply. The research method used is a qualitative descriptive approach, with data collection through literature studies, which include reading articles from books, journals, and other media sources. Labor is generally seen as a positive factor in driving a country's economic development. In conventional economics, educated labor contributes to increased productivity and innovation, while from an Islamic perspective, labor is expected to provide fair and sustainable contributions.